Phylogeny of New World Paspalum (Poaceae, Panicoideae, Paspaleae) based on plastid and nuclear markers - Scataglini, María Amalia (2014)
Phylogenetic analyses of 131 terminals of Paspalum and related genera, based on both plastid and nuclear markers, were performed under maximum parsimony and Bayesian methods. The total evidence analyses generated a hypothesis showing that Paspalum would be monophyletic if Spheneria, Thrasyopsis and Reimarochloa are included within the genus. Paspalum inaequivalve and P. microstachyum, two species of the Inaequivalvia group were related to genus Anthaenantiopsis, excluded from Paspalum, or nested within it by plastid and nuclear markers, respectively. Subgenera Anachyris and Harpostachys were partially recovered as monophyletic assemblages, while subg. Ceresia and Paspalum resolved as polyphyletic. Within subgenus Paspalum, some informal groups were recovered as monophyletic, while others were resolved as paraphyletic or polyphyletic. Phylogenetic relationships among species of Paspalum were partially recovered possibly due to reticulation events among species, autopolyploidization and apomixis; all these processes being common in Paspalum, thus obscuring the infrageneric classification.